Soil Quality Index Analysis of Forest Secondary and Palm Oil Plantation - Nurul Puspita Palupi; Agus Sarjono; Abdul Hanif (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Soil quality greatly determines the ability of the soil in carrying out its functions to support the life of organisms in a sustainable manner. Land use and land management have the role of increasing or decreasing the quality of a land. This research was conducted to determine the index of soil quality in secondary forest land use and oil palm plantations and evaluating the application of the concept of sustainable agriculture to oil palm plantations. This research was carried out from July to October 2019 in Bukit Biru and Loa Ipuh Darat village, Tenggarong and in the Mulawarman University Faculty of Agriculture. This study uses the concept of Minimum Data Set (MDS) with the assessment of several indicators and soil functions. The assessment function is adjusted to the environmental conditions in which the research is conducted. This study shows that secondary forest use has a soil quality index value of 0.638 with Good criteria, and oil palm plantation land use has a soil quality index of 0.592 with Moderate criteria. Oil palm plantations in this study have not yet reached the concept of sustainable agriculture.